Higher prevalence of gestational diabetes in euthyroid women with thyroid autoimmunity who were expecting a female fetus - Madhu Prasai; Manon Lomré; Emna Jelloul; Pierre Kleynen; Flora Veltri; Georgiana Sitoris; Lidia Grabczan; Serge Rozenberg; Kris G Poppe (European Thyroid Journal)
Objective: In the general population, women pregnant with a male fetus (MF) have a higher prevalence of gestational diabetes mellitus (GDM) compared with those pregnant with a female fetus (FF). Some studies suggest a higher prevalence of GDM in euthyroid pregnant women with thyroid autoimmunity (TAI+) compared with women without TAI (TAI−). However, whether the impact of TAI on GDM correlates with fetal gender has not been documented. Design/methods: A single-center cohort study including 1201 women who were screened at a median of 12 (11–14) weeks of pregnancy for thyroid disorders (TSH, free T4 and thyroid peroxidase antibodies (TPOAb)) and at 24–28 weeks for GDM with an oral glucose tolerance test. Exclusion criteria were pre-pregnancy diabetes or hypertension, thyroid dysfunction (treated or untreated) before and after screening, thyroid screening after 20 weeks of pregnancy and assisted pregnancies. The diagnosis of GDM was based on the 2013 WHO criteria, and that of TAI by increased TPOAb levels (≥60 kIU/L). Results: Overall, 622 women were expecting a FF (51.8%) and 579 a MF (48.2%). Seventy-five women were TAI+ (6.2%). The overall prevalence of GDM was 19.6%, 28% in TAI+ women and 19% in TAI− women (P = 0.008 after adjustment for confounders). In women who were expecting a FF, the prevalence of GDM was 34.4% in TAI+ women vs 19.2% in TAI− women; P = 0.002. Conclusions: The prevalence of GDM was increased in euthyroid TAI+ women, but only in the case of pregnancies with a FF. This is opposite to the result observed in the general population and deserves more research to explore the underlying mechanisms.